Inovasi Pembelajaran PAI Berbasis Teknologi: Studi Kasus di Madrasah Aliyah Darul Ishlah Lendang Batah Praya - muaini, muaini (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to examine the form of innovation in Islamic Religious Education (PAI) learning based on technology applied at Madrasah Aliyah Darul Ishlah Lendang Batah Praya and analyze its impact on the effectiveness of the teaching and learning process. This study uses a qualitative approach with a case study method. Data were collected through observation, interviews with PAI teachers and students, and documentation of learning activities. The results of the study indicate that innovation in PAI learning at this madrasah is realized through the use of digital media such as e-learning platforms, interactive learning videos, and online evaluation applications. This innovation has been proven to increase active student participation, strengthen understanding of religious concepts, and build learning independence. The obstacles faced include limited technological infrastructure and the digital capabilities of some teachers. In general, the implementation of technology-based innovation in PAI learning at Madrasah Aliyah Darul Ishlah has made a positive contribution to improving the quality of learning and the relevance of religious education in the digital era.